PENGETAHUAN DAN SIKAP DENGAN TINDAKAN PERAWAT TENTANG PATIENT SAFETY - Pardede, Jek Amidos; Marbun, Agnes Silvina; Zikri, Muhammad (Jurnal Keperawatan Priority, 2020)
Patient Safety is the avoidance, prevention, and repair of unexpected events or overcome injuries from the health care process. Lack of understanding about patient safety can lead to patient safety events due to a lack of knowledge and attitudes of nurses with nurses' actions about patient safety. Knowledge and attitude are needed to improve patient safety and improve the quality of hospital services. This study aims to determine the relationship between nurses' knowledge and attitudes with actions about patient safety in the Datu Beru Takengon Regional General Hospital. The design of this research is the descriptive correlation with the cross-sectional approach. The study population was implementing nurses, amounting to 273 people and the sample in this study amounted to 67 people using Simple Random Sampling sampling techniques. The statistical test used by Spearman-rho. The results obtained there is a relationship of knowledge with the actions of nurses about patient safety where the value (p = 0.033; p <0.05), with a value of r = 0.261 which means that the strength of the relationship is weak and there is a relationship between attitude and nurses' actions about patient safety where the value of p = 0.047; p <0.05 with a value of r = 0.243 which means the strength of the relationship is weak. In conclusion, there is a significant relationship between the knowledge and actions of nurses and there is a significant relationship between attitudes and actions of nurses about patient safety.